Beyond the emergency department: Effects of COVID‐19 on emergency medicine resident education. Issue 3 (28th January 2021) - Ford, Tabitha R.; Fix, Megan L.; Shappell, Eric; Egan, Daniel J.; Mannix, Alexandra; Bailitz, John; Li, Xian; Gottlieb, Michael
Abstract: Background: In December 2019, a novel coronavirus (COVID‐19) caused widespread clinical disease, triggering limited in‐person gatherings and social‐distancing guidelines to minimize transmission. These regulations led most emergency medicine (EM) residency training programs to rapidly transition to virtual didactics. We sought to evaluate EM resident perceptions of the effects of COVID‐19 on their didactic and clinical education. Methods: We performed a cross‐sectional survey study at seven EM residency programs using a mixed‐methods approach designed to understand resident perceptions regarding the impact of COVID‐19 on their educational experience. Quantitative data were presented as percentages with comparison of subgroups, while open‐ended responses were analyzed using qualitative methodology. Results: We achieved a 59% response rate (187/313). The majority of respondents (119/182, 65.4%) reported that the COVID‐19 pandemic had a negative impact on their residency education with junior residents disproportionately affected. A total of 81 of 182 (44.5%) participants reported that one or more of their clinical rotations were partially or completely canceled due to the pandemic. Additionally, we identified four themes and 34 subthemes highlighting the contextual effects of the pandemic, which were then divided into positive and negative influences on the residency experience. The four themes include systems experience, clinical experience, didactic experience, and wellness. Conclusion: Our study examined the impact of COVID‐19 on residents' educational experiences. We found overall mixed responses with a slightly negative impact on residency education, wellness, and clinical rotations, while satisfaction with EM as a career choice was increased. Factors influencing this included systems, clinical, and didactic experiences as well as overall wellness.